Uji Aktivitas Antihiperlipidemia Ekstrak Etanol Daun Notika (Arcboldiodendron calosericeum Kobuski) Terhadap Kadar Kolesterol Total Tikus (Rattus norvegicus) Jantan Galur Wistar - Nuralifah Nuralifah; Wahyuni Wahyuni; Parawansah Parawansah; Ulan Dwi Shintia (Journal Syifa Sciences and Clinical Research, 2020)
Hyperlipidemia is an increase of lipid due to excessive fat consumption, that the intake and alteration of lipid is not balanced. Notika are plants that contain secondary metabolites in the form of flavonoids, tannins, saponins and triterpenoids which are antioxidant compounds that are thought to have the effect of reducing blood lipids. This study aims to determine the effect of ethanol extract of leaves of Notika on decreasing total cholesterol levels in rats induced by egg and propylthiouracil (PTU). This research was experimental in 6 groups, namely 4 groups given ethanol extract of leaves of Notika at a dose of 50 mg/kgBB, 100 mg/kgBB, 200 mg/kgBB, and 300 mg/kgBB, one group was given Na CMC 0.5% as a negative control, and one group was given simvastatin 10 mg as a positive control. The results showed that the ethanol extract of the leaves of Notika significantly reduced the total cholesterol level of rats with a significant value 0.05 and 300 mg/kgBB is an effective dose to reduce total cholesterol level.